Penerapan Model PBL Dalam Upaya Meningkatkan Kemampuan Scientific Reasoning Siswa Sekolah Dasar - Iwan Usma Wardani; Ida Bagus Putu Arnyana; I Wayan Suastra (Universitas Hamzanwadi, 2022)
The use of learning models that are not appropriate can cause students difficulties in stating a scientific reason. Students need to practice scientific reasoning skills such as thought processes to examine, understand, and criticize objects or phenomena. Scientific reasoning is one of the learning outcomes that should be trained on students because high scientific reasoning will affect students in making decisions and solving problems. It takes seriousness in practicing scientific reasoning skills. So the teacher must choose the appropriate learning approach. Scientific reasoning skills can be trained by teachers by applying inquiry-based learning, one of which is Problem Based Learning (PBL). PBL has five steps, namely: (1) orienting students to problems, (2) organizing students to learn, (3) guiding group investigations, (4) developing and presenting work, and (5) analyzing and evaluating the solution process. problem. The PBL model is a learning approach that emphasizes scientific learning, because by being given a problem and then students are required to solve it, students' scientific reasoning abilities will develop